Hijrah ke Manhaj Salaf: Ekspresi dan Negoisasi Kesalehan Kaum Muda Urban - Syamsul Rijal; Ade Masturi (Institut Agama Islam Negeri Kendari, 2022)
This article examines the trend of hijrah among young Muslims by taking the case of the participants at the Nurul Iman Mosque, Blok M Square, Jakarta. They actively participate in regular Islamic learning held at the mosque and frame their participation as a form of hijra (migration) to the Salafi path. Our study draws on an anthropological approach by conducting participatory observation and in-depth interview. We explore the young Muslim motivations and initial introduction to Salafism. We examine how they view hijrah and how they practice it in their individual and social lives. The result of this research shows that the Salafi youths view hijrah as a process to become better Muslims. In practice, they have applied the teachings of Salafism in their everyday lives in terms of behaviour, dressing, and interaction. The narrations of the Salafi youths suggest that they have undertaken various forms of negotiations in practicing their hijrah